Comparison of sulfur hexafluoride and air for donor attachment in descemet stripping endothelial keratoplasty in patients with pseudophakic bullous keratopathy - Torun Acar, Banu; Müftüoğlu, Orkun; Acar, Suphi (Lippincott Williams & Wilkins, 2014)
Purpose:The aim of this study was to evaluate the clinical efficacy and safety of sulfur hexafluoride (SF6) as a tamponading agent after donor placement during Descemet stripping endothelial keratoplasty (DSEK) surgery and to compare the outcomes with those of air.Methods:Forty-four eyes of 44 consecutive patients who underwent DSEK were included in the study. Air was used in 22 eyes of 22 patients (air group), and SF6 was used in 22 eyes of 22 patients (SF6 group) to attach the donor lenticule. The complications, corrected visual acuity (CVA), and the endothelial cell density (ECD) results were compared between these 2 groups.Results:Six eyes had graft dislocation in the air group that underwent successful rebubbling on postoperative day 1. There was no graft dislocation in the SF6 group. There was no other complication observed in both the groups. The mean increase in the CVA was 1.09 0.36 logarithm of the minimum angle of resolution in the air group, whereas it was 0.80 +/- 0.57 logarithm of the minimum angle of resolution in the SF6 group. The mean increase in the CVA was not statistically different between the 2 groups (P = 0.060). Compared with the mean ECD in donor grafts, the mean decrease in the ECD was 222 +/- 86 (44%) cells per square millimeter in the air group and 178 +/- 52 (39%) cells per square millimeter in the SF6 group at the 1-year follow-up. The mean decrease in the ECD was statistically significantly higher in the air group compared with that in the SF6 group (P = 0.049).Conclusions:SF6 is comparable to air for attaching the donor graft as a tamponading agent in DSEK surgery.
WOS: 000331530700001
PubMed ID: 24452211
Keywords: Descemet Stripping Endothelial Keratoplasty; Sulfur Hexafluoride; Endothelial Cell Density